Time remote - Sommer, Carl, 1930-; Budwine, Greg (Houston, TX : Advance Pub., 2000)
When Christopher gets a remote controller that enables him to skip ahead in time, he tries to use it to avoid his problems.
Keywords: Time travel -- Fiction; Conduct of life -- Fiction